Investigating the intention to continue using software at work in digital transformation context: Integrating task - technology fit into technology continuance theory - Bùi Thành Khoa; Trần Trọng Huỳnh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
After firms implement new software systems, it is crucial to encourage workers to continue using them. The purpose of this research is to examine the efficacy of an integrated Task-Technology Fit factor into Technology Continuance Theory (TCT) in elucidating the reasons why workers maintain their use of an organizational software. The data was gathered via a survey of 307 people employed by various organizations that used the software in their professional activities. Structural Equation Modeling using Partial Least Squares (PLS-SEM) was used to examine the study model. Intention to continue using in software was favorably predicted by satisfaction, attitude, and perceived usefulness; and task-technology fit positively impacted attitude and satisfaction of software users. The findings provided role of task-technology fit as businesses applied the softwares to enhance their performance in digital transformation process. Furthermore, some actionable managerial implications were proposed for encouraging enterprises to consistently implement software systems in business process.